A sign of affection. 3 - Dashiell, Christine, 1984-; Vanstiphout, Carl; Blakeslee, Lys, 1985- (Kodansha Comics, an imprint of Kodansha USA Publishing, 2021)
Deaf college student Yuki is diving into her newfound romance with Itsuomi, a classmate she met on the train who doesn't tiptoe around her disability, and also happens to be extremely hot. But his handsome looks mean girls tend to throw themselves at him, and he's unintentionally broken hearts before. Can Yuki draw out Itsuomi's true intentions? And is he even interested in romance, or is his focus on an entirely different kind of dream?